Cervical cancer awareness, perception, and attitude among tertiary health institution students in northeastern Nigeria - Muhammad, Zakia B.; Ezenkwa, Uchenna S.; Imoudu, Iragbogie A.; Katagum, Dauda A.; Usman, Iliyasu; George, Sophia H. L.; Schlumbrecht, Matthew; Audu, Bala M. (Frontiers in Oncology, 2024)
The devastating scourge of cervical cancer in Africa is largely due to absence of preventive interventions driven by low awareness and poor perception about the disease in the continent. This work is a preliminary effort towards understanding key social drivers promoting this disease in our immediate environment with a view to mitigating it.Female students of two tertiary health institutions in Azare, North-eastern Nigeria were approached to participate in this cross-sectional descriptive study. A structured selfadministered questionnaire was administered to consenting participants and covered questions on their socio-demographics, awareness, perception and attitude about/towards cervical cancer and its prevention. The responses were scrutinized for coherency and categorized into themes using summary statistics while chi-square test was used to determine the association between awareness of cervical cancer and participant age, marital status, religion, screening uptake, and willingness to screen.Awareness of cervical cancer was recorded among 174/230 (75.7%) respondents who enrolled in this study. 117 (67.2%) knew that it is preventable, but only 3 (1.3%) respondents had undergone screening. Amongst the aware participants, 91 (52.3%) and 131 (75.3%) knew that sexual intercourse and multiple sexual partners are risk factors for the disease, respectively. On the other hand, knowledge of the aetiology was poor; 82 (47.1%) respondents who knew it was preventable had heard about human papilloma virus (HPV), while 72 (41.4%) knew that HPV causes cervical cancer. Most (78%) of the participants expressed willingness to take human papilloma virus vaccine or undergo screening (84.6%) if made available to them. Awareness was significantly associated with participants' age (p = 0.022) and willingness to screen (p = 0.016).This study revealed discordance between awareness and knowledge about cervical cancer.Educational initiatives reflective of population perception/knowledge of cervical cancer are needed to mitigate the rising incidence of this disease, especially among female healthcare providers.